Evaluasi Penggunaan Antibiotik pada Pasien Pneumonia Komunitas Menggunakan Metode Gyssens - Dwi Aulia Zahra; Rezlie Bellatasie; Putri Ramadhani; Widya Kardela; Wulan Panduwi Melasari; Hendri Satria Kamal Uyun (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2026)
Pneumonia is an infection of the lower respiratory tract that remains a significant cause of morbidity and mortality globally, including in Indonesia. Irrational antibiotic use among pneumonia patients can promote the development of antibiotic resistance, elevate treatment expenses, and adversely affect clinical outcomes. This study aims to evaluate the rationality of antibiotic use among patients with community-acquired pneumonia in the internal medicine inpatient ward of a government hospital in Padang City, West Sumatra, using the Gyssens method. This study employed a descriptive, observational, cross-sectional design from January to March 2025. A total of 29 patients were selected based on the inclusion criteria. The most commonly prescribed antibiotics were third-generation cephalosporins (especially ceftriaxone and cefixime), macrolides (azithromycin), and fluoroquinolones (levofloxacin). The results showed that 18 patients (62.07%) used antibiotics rationally (category 0), while 11 patients (37.93%) used antibiotics irrationally in categories IIIa (17.24%), IIa (17.24%), and I (3.45%). There still needs to be better monitoring of antibiotic use by healthcare workers to improve the accuracy of antibiotic choices for patients.